International Terms for Recognition, Validation and Accreditation of Prior Learning: Comprehensive Reference Document (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
The terminology for the recognition, assessment, validation, and credentialing of prior knowledge and skills has evolved as policies and practices have grown around the world.  Different regions, countries, and institutions have used various terms to describe the recognition, assessment, and validation of knowledge and skills acquired through informal, nonformal, and personal learning.  All these terms generally refer to the assessment and recognition of knowledge, skills, and competencies acquired through work experience, informal education, military service, community involvement, and self-study. Terminology always reflects fundamentally different philosophies, methodologies, and power structures for engaging with learners’ experiences. The words we use also vary and continue to change by region and institution. Still, the underlying concept remains consistent: providing formal recognition to make visible skills and knowledge that have often gone unnoticed.